Macroeconomic Stabilization of the Eurozone in 1999-2013 - Urbanowicz , Zuzanna (Studia Oeconomica Posnaniensia, 2015)
The main aim of this article is to measure the processes of macroeconomic stabilization in the Eurozone as a whole and in the group of 11 countries which have been members of the economic and monetary union since its creation (Germany, Ireland, Belgium, Spain, Luxembourg, the Netherlands, Austria, Portugal, Finland, Italy, and France). The study used a quarterly time series for the period 1st qr. 1999 to 3rd qr. 2013. To measure macroeconomic stabilization, descriptive statistics and multidimensional analysis were applied. The multidimensional analysis made it possible to create a synthetic indicator of macroeconomic stability and to generate a ranking of countries based on this criterion. An analysis of the data showed that the process of macroeconomic stabilization proceeded best in the Austrian economy, which achieved relatively good results by striving to realize all of the stabilization purposes. Those countries which failed some of the stabilization policy objectives were lower in the ranking. In addition, it was found that the aggregate indicators relating to the economic situation of the euro area significantly "mask" the differences in the levels of various macroeconomic variables in the individual countries of the common currency area. This means that the aggregate indicators cannot be the basis for a reliable assessment of individual economies among the Eurozone member states.